AB1117-HPR Evaluation of Patient Reported Outcome Data Following Persistent Musculoskeletal Pain Service Redesign. (15th July 2016) - Light, H.; Firth, J.; Kinsey, K.
Abstract : Background: Persistent musculoskeletal pain (lasting >3 months) is common in the UK and Europe. Following an independent review of service provision, a person-centred, integrated pathway of bio-psychosocial care was commissioned in Oldham, UK. A stepped care model was introduced comprising a single point of access to multidisciplinary care including psychological medicine, prescribing advice and exercise classes. Objectives: To evaluate improvements in pain reported by patient and clinicians discharged from the service and compliance with data capture in the first 6 months. Methods: Outcome data was collected on all patients opting in between 1st June-30th November 2015 including Pain Self-Efficacy Questionnaire (PSEQ) and DoloTest scores on entry and discharge and Clinical Global Impression-Improvement scale (CGI-I) on discharge. PSEQ scores range from 0–60; lower scores reflect little/ no confidence in performing daily activities. DoloTest scores range from 0–800 with lower scores reflecting a lower impact on quality of life. CGI-I is a clinician assessment of patient improvement, scores range from 1–7, with low scores reflecting an improvement and high scores reflecting deterioration. Results: 369 patients opted in throughout the 6 month period, of which 170 (46%) have been discharged. Mean PSEQ score on entry was 17.3 (n=163), which improved to 30.7 (n=50) on discharge. 86% had an improvement in their PSEQ scores with 60% benefiting from a clinically significant improvement. The mean improvement was a score of 17, the mean improvement of significantly improved patients was 22.2 points. Mean DoloTest score on entry was 546.5 and 431.3 on discharge. 70% had an improvement in their DoloTest results; mean improvement was 154 points. There is no available benchmark for a clinically significant improvement for DoloTest. 72% of patients assessed using CGI-I were scored as having very much or much improved. 59 patients (35%) had missing discharge data. Reasons included patients failing to attend follow ups or opting out (46%), stepping up care up to secondary care provision for patients with complex needs (25%), and missing data, unknown (29%). 13 (8%) patients were discharged at first appointment therefore no follow up assessments were completed. Conclusions: In all assessments, the majority of patients improved throughout their treatment. A change in PSEQ score around 10 is considered clinically significant. Of 7 patients with no improvement in PSEQ score, 2 scored <20 indicating their focus on pain could influence their willingness to engage in activity. Of the remaining 5 patients, 3 had high initial scores (>40) thought to be incongruent with requiring a pain management programme. Missing data affected the evaluation and qualitative work is being undertaken to understand the reasons for this and to inform strategies to increase data capture. Disclosure of Interest: None declared